Volksraad (People Council): Radicale Concentratie Political Arena and National Fraction, 1918-1942 - Nazirwan Rohmadi; Warto Warto (Humaniora, 2019)
This paper discusses the legislative institutions callled Volksraad established by the Dutch East Indies, which further used by the nationalist-moderate to achieve the national  independence of Indonesia. Historical method was used in this research. The historical method is distinguished into several stages, namely heuristic, critic, analysis, and historiography. Indonesia’s political figures established Radicale Concentratie to unite in order to achieve independence. Radicale Concentratie put a great pressure on the Dutch East Indies government. Radicale Concentratie no longer operated because of some conflicts that occurred among its members and the arrests done by the Dutch East Indies government. Radicale Concentratie’s struggle was continued by National Fraction which was established on 27 January 1930. The proposition of National Fraction that was fulfilled was the change in the nomenclatur of Indlander to Indonesisch. National Fraction often turned down the budget plan proposed by the Governor-General in preparing for the Second World War. This is because the Dutch East Indies fleet was funded by Indonesian taxes and the taxes were planned to be increased in order to win the war.